A 3D Corncob-based interfacial solar evaporator enhanced by environment energy with salt-rejecting and anti-corrosion for seawater distillation. (1st March 2023) - He, Jinmei; Ge, Jianwei; Pang, Yajie; Shen, Lei; Wu, Yaxin; Lv, Yanqing; Zhang, Bin; Peng, Lei; Yang, Jie; Qu, Mengnan
Abstract: Biomass-derived, carbon converted from renewable biomass materials via the carbonization process, has been widely investigated for interfacial solar evaporators and is deemed a promising choice for solar desalination. However, salt accumulation at the evaporation interface is a great challenge. Studies show that the surface wetting and antifouling ability of carbonized-biomass, affects solar absorption, water supply, and water evaporation. In this paper, a simple two-step strategy completely different from carbonization is proposed for efficient solar evaporation and seawater desalination. In this regard, an interfacial solar evaporator is prepared based on the corn cob. The evaporator makes the best use of the raw three-dimensional interconnected fiber network structure, which extremely promotes the collection of solar energy, sufficient water supply, and vapor escape at the evaporation interface. Owing to the decrease in evaporation enthalpy and drawing energy from the environment, the evaporation rate and the photothermal conversion efficiency of proposed the evaporator reached 1.68 kg·m −2 ·h −1 and 99.32 % under solar irradiation intensity of 1 kW·m −2, respectively. The performance of the proposed scheme was investigated under various salinity levels and a great salt-rejecting and anti-corrosion performance was achieved. This simple strategy is a promising candidate for preparing biomass-based interfacial solar evaporators in practical applications.